LuciPHOr2: site localization of generic post-translational modifications from tandem mass spectrometry data - Fermin, Damian (Bioinformatics, 2015)
We present LuciPHOr2, a site localization tool for generic post-translational modifications (PTMs) using tandem mass spectrometry data. As an extension of the original LuciPHOr (version 1) for phosphorylation site localization, the new software provides a site-level localization score for generic PTMs and associated false discovery rate called the false localization rate. We describe several novel features such as operating system independence and reduced computation time through multiple threading. We also discuss optimal parameters for different types of data and illustrate the new tool on a human skeletal muscle dataset for lysine-acetylation. Availability and implementation: The software is freely available on the SourceForge website http://luciphor2.sourceforge.net. Contact: hyung_won_choi@nuhs.edu.sg, nesvi@med.umich.edu Supplementary information: Supplementary data are available at Bioinformatics online.